Simulation of an IoT Based Smart System for Monitoring Hand Hygiene of Medical Personnel in Hospitals - Elsyea Adia Tunggadewi; Sisca Dina Nur nahdliyah; Hadi Prayitno (International Journal of Computer, Network Security and Information System, 2024)
Improving hand hygiene of medical personnel in hospitals is one of the main steps in preventing nosocomial infections which can threaten patient safety. However, based on WHO data, only around 40% of medical personnel consistently comply with hand hygiene protocols. Obstacles such as lack of supervision and technological limitations also worsen this condition. Therefore, this research proposes the development of an Internet of Things (IoT) based system that can monitor the hand hygiene of medical personnel in real-time, as an effort to increase compliance and support more effective hand hygiene management in the hospital environment. This research aims to design an intelligent IoT system that is able to detect and record the hand hygiene activities of medical personnel automatically, based on predetermined hand hygiene protocols. This system will also be equipped with data analysis features to help hospital management evaluate the level of medical personnel's compliance with hygiene standards. By utilizing sensor technology, this system is expected to be able to provide innovative, efficient and integrated solutions, so that it can support more optimal hygiene management in health facilities. The research method consists of three main stages. The first stage is a needs analysis and literature study to understand relevant hand hygiene standards and IoT technologies. The second stage involves system design, including virtual microcontroller-based hardware modeling, sensor simulation, and software development in a simulation environment. The third stage is system simulation and performance testing in a virtual hospital environment to evaluate its effectiveness. An iterative approach is applied to ensure the simulation results comply with theoretical user needs and applicable standards.